Handbook of Vocational Rehabilitation and Disability Evaluation Application and Implementation of the ICF - Escorpizo, Reuben.; Escorpizo, Reuben.; Brage, Sören.; Brage, Sören.; Homa, Debra.; Homa, Debra.; Stucki, Gerold.; Stucki, Gerold. (Handbooks in Health, Work, and Disability,, 2015)
For persons with chronic illnesses and disabling injuries, work prospects--especially for meaningful work with decent conditions--have traditionally been poor. With global efforts from the UN, WHO, ILO, and other bodies focusing attention on this wide-reaching issue, innovative tools are needed to translate large-scale goals into real-world outcomes.  The framework offered by the Handbook of Vocational Rehabilitation and Disability Evaluation highlights the complex challenges and opportunities involved in enabling re-entry into the workforce. Geared to ICF (International Classification of Functioning, Disability, and Health) standards, this timely reference outlines current science-based methods in assessing impairment and capabilities and emerging approaches to management specifically relating to work participation. Separate chapters are devoted to evaluation and rehabilitation guidelines for individuals with brain injury, chronic musculoskeletal pain, mental illness, and other disabling conditions. And the chapters on ICF-based functioning measurement review the data on widely-used clinician- and patient-reported instruments and the recent Work Rehabilitation Questionnaire (WORQ). Featured in the Handbook: The impact of chronic disease on work participation and its implications for intervention and management. Vocational assessment and job placement. Spinal cord injury: vocational rehabilitation and disability evaluation. Critical issues for mental health management in vocational rehabilitation. Clinician-reported outcome measures: experiences from multicenter follow-up. ICF-based tools in rehabilitation toward return-to-work. The Handbook of Vocational Rehabilitation and Disability Evaluation is of critical interest to researchers, educators, and students in disability- and work-related fields. It is also a practical resource outside the campus setting, aiding those providing services to, as well as policymakers involved in improving the lives of, persons with disabilities.  .